2011
DOI: 10.1097/adm.0b013e3181db69ef
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Characteristics and Risky Behaviors Among the Iranian Opium and Opium Dross Addicts

Abstract: These results indicated the need for more intensive and effective care for the opioid addicts in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Our analysis showed that opium was the most frequently used drug among students (45.6% of the users of illicit drug). In general, because of the domestic reasons and high availability due to the close proximity to Afghanistan, opium consumption is more common in Iran ( 24 ). Therefore, in addition to differences in the prevalence rate, the pattern of substance use in Iranian students is completely different from students of western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that opium was the most frequently used drug among students (45.6% of the users of illicit drug). In general, because of the domestic reasons and high availability due to the close proximity to Afghanistan, opium consumption is more common in Iran ( 24 ). Therefore, in addition to differences in the prevalence rate, the pattern of substance use in Iranian students is completely different from students of western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, 38% of 18-25 year-old adolescents annually drink alcohol and 11% are heavy drinkers [9]. Although alcohol use is illegal due to Islamic restrictions in Iran, its use has increased among young Iranians [10,11]. There has been different reports regarding prevalence of alcohol use among Iranian students, varying from 7% to higher in other studies [12,13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consequently, this has made opium and other drugs easily available for Iranians [1,2]. This put more people at risk of drug addiction and drug trafficking related crimes, and so more related incarceration [3,4].…”
Section: Introductionmentioning
confidence: 99%